PERAN KETUA VIHARA DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA DI DESA NGABLAK KECAMATAN CLUWAK - Arif Susilo; Santi Paramita; Sudarto * (Pascasarjana Universitas Hindu Indonesia, 2024)
The values ??of religious moderation must be understood as a balance related to respect for people who have different beliefs, harmony and tolerance. One way of creating or realizing peace is because it is able to maintain balance and tolerance. The aim of this research is to determine the role of the Vihara head in minimizing the problems of religious moderation in Ngablak Village, Cluwak District, Pati Regency. This research uses a qualitative descriptive approach with data collection techniques of observation, interviews and documentation, information consisting of several religious figures in Ngablak Village, Cluwak District, Pati Regency. The results of the research show that the Head of the Vihara is a figure who can be emulated and guides the community. The role played by the Head of the Vihara in instilling the values ??of religious moderation in Ngablak Village is by instilling a positive attitude towards the community regarding differences and views or opinions of the community regarding different ways of worship and other religious activities. Meanwhile, the strategy carried out by the Head of the Vihara to minimize the problems of religious moderation in Ngablak Village is by opening up the role of dialogue, socialization, routine studies and social activities.